Por quien rueda la pelota - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Dog Man., 2020)
The Supa Buddies have been working hard to help Dog Man overcome his bad habits. But when his obsessions turn to fears, Dog Man finds himself the target of an all-new supervillain! Meanwhile, Petey the Cat has been released from jail and starts a new life with Li'l Petey.